Epidemiology of Chlamydia psittaci in pet birds associated with psittacosis cases in humans - Ferreira, Vivian Lindmayer (2016)
Zoonosis represent the majority of emerging infectious diseases, which have variable occurrence according to biological, environmental, socio-economic and cultural factors. With respect to socio-cultural factors, a growing practice in Brazil is keeping exotic animals as pets. These can have significant role in the spread of pathogens with zoonotic potencial, such as Chlamydia psittaci, etiologic agent of chlamydiosis in birds and psittacosis in humans. The Psittaciformes are the main order of birds affected by C. psittaci and is the most commonly kept as a pet. Avian chlamydiosis is endemic in Brazil; however, few studies have been conducted regarding its zoonotic potential. In human, psittacosis can lead to atypical pneumonia, however, due to difficulties related to laboratory diagnosis and the relative lack of knowledge by health professionals about this disease, its prevalence in the country is still unknown. In this context, this study aimed to determine the occurrence of C. psittaci in patients with psittacosis symptoms attended at the Ambulatory of Tropical Diseases and Zoonosis of the Infectology Institute Emilio Ribas (IIER). In addition, establishing the epidemiological link with birds and evaluate risk factors related to this zoonosis. Therefore, serum samples from eligible patients were collected in order to be tested for C. psittaci IgA, IgM and IgG antibodies. At the same time, biological samples from any species of birds related to suspected cases of psittacosis were collected for molecular analysis of C. psittaci. Among the eligible patients in this study, 27% (10/37) were classified as confirmed cases of psittacosis; 13.5% (5/37) as probable and 59.5% (22/37) as discarded. Pneumonia (p = 0.004), cough (p = 0.002) and chills (p = 0.011) were statistically significant when comparing with those patients in which psittacosis was discarded. With reference to the epidemiological link with birds, 73% (11/15) of the confirmed/probable cases had domiciliary contact with birds and 27% (4/15) had occupational contact. In addition, 47% (7/15) patients had contact with infected birds in which C. psittaci was laboratorial confirmed; from another 47% (7/15) of the cases, biological samples of the birds related to the patient could not be obtained, and in 6% (1/15) of the cases C. psittaci was not detected in the bird hosts evaluated. In addition, several confirmed/probable cases reported having close contact with the birds as handling (100%, 15/15), keeping the bird in the shoulder (67%, 10/15), kissing the bird (40%, 6/15) and sharing the food with the bird (13%, 2/15), practices that facilitate diseases transmission. Human and animal health care providers have an important role to play in identifying specific factors affecting the health of their patients and should work together. Conjointly efforts would increase the understanding on zoonotic disease and would, ultimately, improve prevention and control strategies